2023
DOI: 10.3390/jcm12237318
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Effects of an Oral Supplementation of Bromelain and Curcugreen in Patients with Focal Diabetic Macular Edema

Adriano Carnevali,
Sabrina Vaccaro,
Massimiliano Borselli
et al.

Abstract: Diabetic retinopathy (DR) is one of the most severe diabetes-related complications, and macular edema stands as the primary contributor to the loss of central vision in individuals diagnosed with diabetes mellitus. The purpose of this study was to investigate the anatomical and functional effects of the oral administration of bromelain and curcugreen in patients controlled by therapy with non-proliferative DR presenting focal edema. Patients were enrolled and divided into two groups: group A (n = 18) received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…One of the most interesting nutraceuticals, bromelain, is widely used for the prevention or co-management of numerous diseases that are characterized by the presence of inflammation, edema, and algesia. Although several clinical trials have demonstrated the efficacy of bromelain supplementation in the reduction in pain [ 20 ], inflammation [ 21 ], and edematous components [ 22 ], its commercial cost is high, while the isolation and purification of bromelain from pineapple (fruit, core, stems, and leaves) is an open issue, making up 70–90% of the final extract production cost [ 23 ]. Moreover, notwithstanding the advent of novel and viable protein purification methods such as membrane filtration, reverse micellar systems, aqueous two-phase extraction, and chromatographic techniques, as well as the development of new biotechnological processes aimed at reducing production costs, various limitations persist.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most interesting nutraceuticals, bromelain, is widely used for the prevention or co-management of numerous diseases that are characterized by the presence of inflammation, edema, and algesia. Although several clinical trials have demonstrated the efficacy of bromelain supplementation in the reduction in pain [ 20 ], inflammation [ 21 ], and edematous components [ 22 ], its commercial cost is high, while the isolation and purification of bromelain from pineapple (fruit, core, stems, and leaves) is an open issue, making up 70–90% of the final extract production cost [ 23 ]. Moreover, notwithstanding the advent of novel and viable protein purification methods such as membrane filtration, reverse micellar systems, aqueous two-phase extraction, and chromatographic techniques, as well as the development of new biotechnological processes aimed at reducing production costs, various limitations persist.…”
Section: Discussionmentioning
confidence: 99%